Tandem Catalysis by Palladium Nanoclusters Encapsulated in Metal–Organic Frameworks - Li, Xinle; Guo, Zhiyong; Xiao, Chaoxian; Goh, Tian Wei; Tesfagaber, Daniel; Huang, Wenyu (ACS catalysis, 2014)
A bifunctional Zr-MOF catalyst containing palladium nanoclusters (NCs) has been developed. The formation of Pd NCs was confirmed by transmission electron microscopy (TEM) and extended X-ray absorption fine structure (EXAFS). Combining the oxidation activity of Pd NCs and the acetalization activity of the Lewis acid sites in UiO-66-NH2, this catalyst (Pd@UiO-66-NH2) exhibits excellent catalytic activity and selectivity in a one-pot tandem oxidation-acetalization reaction. This catalyst shows 99.9% selectivity to benzaldehyde ethylene acetal in the tandem reaction of benzyl alcohol and ethylene glycol at 99.9% conversion of benzyl alcohol. We also examined various substituted benzyl alcohols and found that alcohols with electron-donating groups showed better conversion and selectivity compared to those with electron-withdrawing groups. We further proved that there was no leaching of active catalytic species during the reaction and the catalyst can be recycled at least five times without significant deactivation.